Plant dermatitis: Asian perspective - Anthony Teik Jin Goon; Chee Leok Goh (Wolters Kluwer Medknow Publications, 2011)
Occupational and recreational plant exposure on the skin is fairly common. Plant products and extracts are commonly used and found extensively in the environment. Adverse reactions to plants and their products are also fairly common. However, making the diagnosis of contact dermatitis from plants and plant extracts is not always simple and straightforward. Phytodermatitis refers to inflammation of the skin caused by a plant. The clinical patterns may be allergic phytodermatitis, photophytodermatitis, irritant contact dermatitis, pharmacological injury, and mechanical injury. In this article, we will focus mainly on allergy contact dermatitis from plants or allergic phytodermatitis occurring in Asia.